2017
DOI: 10.1007/s00418-017-1569-1
|View full text |Cite
|
Sign up to set email alerts
|

Tropism, intracerebral distribution, and transduction efficiency of HIV- and SIV-based lentiviral vectors after injection into the mouse brain: a qualitative and quantitative in vivo study

Abstract: Lentiviruses are suitable to transfer potential therapeutic genes into non-replicating cells such as neurons, but systematic in vivo studies on transduction of neural cells within the complete brain are missing. We analysed the distribution of transduced cells with respect to brain structure, virus tropism, numbers of transduced neurons per brain, and influence of the Vpx or Vpr accessory proteins after injection of vectors based on SIVsmmPBj, HIV-2, and HIV-1 lentiviruses into the right striatum of the mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…Brains of female C57B1/6 mice (C) Tracking the transduction of various viral vectors in neurons after being injected into mice brains (Hlavatý et al, 2017).…”
Section: #S5mentioning
confidence: 99%
“…Brains of female C57B1/6 mice (C) Tracking the transduction of various viral vectors in neurons after being injected into mice brains (Hlavatý et al, 2017).…”
Section: #S5mentioning
confidence: 99%
“…Furthermore, although researchers have sought to remove accessory viral proteins from LV systems due to biosafety concerns, it has been demonstrated that LV tropism and efficacy can be altered by the inclusion of vpx . In in vivo studies in mice and rats, SIV-based LVs lacking accessory proteins have demonstrated robust tropism towards neurons [ 95 , 102 ]; however, Hlavaty and colleagues were able to modify the vector to preferentially target glial cells in mice via the introduction of the vpx gene in the packaging construct [ 102 ]. In addition, the accessory Vpx protein has been exploited to manipulate the early phases of lentiviral infection.…”
Section: Lentiviral Vector Systems Generated Based On Non-human Lementioning
confidence: 99%